Implementation of Seaweed Cultivation Village Policy in Southeast Maluku - Dinar Roosdinar; Asep Sumaryana; R. Ahmad Buchari (Eduvest - Journal of Universal Studies, 2025)
Government policies in supporting the management of fishery and marine resources based on the Blue Economy have one of the priority programs, namely the development of environmentally friendly aquaculture in freshwater, brackish and marine waters. Policies are made in the form of cultivation village development activities. The development of seaweed cultivation villages in Southeast Maluku is a policy made to support increased production and maintain the preservation of germplasm, especially seaweed which is considered to have high quality. The development of seaweed cultivation in Southeast Maluku is supported by the high potential it has but with a low utilization rate and this has an impact on the small production of seaweed in Southeast Maluku in supporting national seaweed production. This study aims to find out the process of implementing the seaweed cultivation village policy in Southeast Maluku. The research method used is qualitative descriptive, namely through observation, interviews and documentation studies from journals, reports and news media relevant to the research topic. The results of the research obtained are that the implementation of the seaweed cultivation village policy in Southeast Maluku has not been running optimally, sustainability factors with environmentally friendly cultivation have been implemented but have not been fully implemented, downstream is still constrained by the absence of investors and the cooperation of related parties in advancing the seaweed industry in Southeast Maluku,